PENERAPAN STRATEGI IMC (INTEGRATED MARKETING COMMUNICATION) SYARIAH HOTEL SOLO - Nugroho, Harits Suryo; Wisudawanto, Rahmat; Musta'an, Musta'an (JURNAL KOMUNITAS, 2022)
The research entitled "IMC Strategy (Integrated Marketing Communication) of Syariah Hotel Solo in forming a positive image" aims to describe how Syariah Hotel Solo implements IMC. This research method is descriptive using a qualitative approach. This study took two respondents who work at the Syariah Hotel Solo using interview and observation techniques. The interview technique was carried out in a structured manner using interview guidelines. The data analysis of this research is descriptive. Based on the study results and discussion, Syariah Hotel Solo is quite effective in implementing the IMC strategy. By implementing various aspects that support the implementation of IMC, namely: 1) Advertising, 2) Personal selling, 3) Public relations, 4) Direct marketing, and 5) Sales promotion.